Piękny czy dobry? Moralny wymiar upiększania ciała - Napiwodzka-Bulek, Karolina (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The main purpose of the article is to point outsome relations between beauty and good in contemporary reality. The main question that arises here is as follows: is the relationship of beauty and moral good still relevant? The concept presented in the thesis refers to the ancient idea of kalokagathia. It stated that beauty is inseparable from moral good. As far as this ancient perspective is concerned, it can be treated as the background for contemporary considerations about the main issue of beauty and good. The article refers to the concept of aestheticization by Wolfgang Welsch. He defines aesthetics as the primary guiding value, where as experience and entertainment have become the guidelines for contemporary culture. Moreover, the thesis mentions the concept of the consumer society and new ethics of the relation to the body as it is described by Jean Budrillard. Then the narration of the article focuses on the following problem: in what sense can we talk nowadays about moral motivation for beauty treatments of body? One assumption leads to the case of looking after one’s body. Another point of view mentions the need of harmony which manifests itself in beautiful body. Eventually, the central question emerges whether contemporary practice of beautifying the body can be a part of the concept of the good life or not.